Enhancing Competitiveness of Coffee Growers in Ituango, Colombia, through Science, Technology, and Innovation: “The Coffee Grower’s Laboratory Initiative” - Marcela Martínez-Castaño; Luis Esteban Pérez-Pérez; Deisy Johana Gómez-Quintero; Cecilia Gallardo-Cabrera; Juliana Rojas-Gallardo; María Alexandra Quirama-Rivera; Gabriela Sánchez-Betancur; Edilson Alexis Zapata-Uribe; Claudia Patricia Posso-Carvajal; Diana María Tabares-Guevara; Andrés Julián Tobón-Agudelo; Juan Camilo Zambrano-Sánchez; et al. (Proceedings)
Different actors have observed divergences and imbalances related to quality understanding and value appropriation in the coffee value chain. Reducing this gap and ensuring sustainability requires innovative strategies. The “Coffee Grower’s Laboratory” in Ituango, Colombia, was established to enhance local coffee farmers’ capacities in science, technology, and innovation. Over 13 participatory methodologies were developed with design thinking to facilitate knowledge exchange between the farmers’ traditional expressions and international commercial practices. Key methodologies included brand co-creation (Artesanato), roast curves (Anatomy of Roasting), roaster operation (The Roaster’s Journey), understanding beans (Know the Bean), and coffee tasting (Deliciousometer). Additionally, methodologies for strengthening intra and interpersonal skills, such as self-care (Crossing the River) and empowerment (The Four Pillars of Trust), were included. Altogether 302 coffee farmers participated. We co-created a community brand, Itucafé, promoted on social media to highlight the farmers’ traditions and innovations nationally and internationally. Farmers, who previously sold only washed parchment coffee, now process, taste, and sell their coffee directly to buyers. Selling directly to buyers increased coffee growers’ profits to around 50% through the “Coffee Grower’s Laboratory”, compared to the less than 10% they earned previously. They also experiment with new fermentations using local fruits, creating unique sensory profiles for more competitive pricing. The “Coffee Grower’s Laboratory” has strengthened the coffee community’s capabilities and competitiveness, enhancing the visibility and recognition of Ituango coffee. It provides an ideal environment for continuous training and producer-buyer relationships, serving as a replicable model for other coffee-producing regions in Colombia.